Treatment outcome of smear-positive pulmonary tuberculosis patients in Tigray Region, Northern Ethiopia - Berhe, Gebretsadik (BioMed Central, 2012)
BACKGROUND: Monitoring the outcome of tuberculosis treatment and understanding the specific reasons for unsuccessful treatment outcome are important in evaluating the effectiveness of tuberculosis control program. This study investigated tuberculosis treatment outcomes and predictors for unsuccessful treatment outcome in the Tigray region of Ethiopia. METHODS: Medical records of smear-positive pulmonary tuberculosis (PTB) patients registered from September 2009 to June 2011 in 15 districts of Tigray region, Northern Ethiopia, were reviewed. Additional data were collected using a structured questionnaire administered through house-to-house visits by trained nurses. Tuberculosis treatment outcomes were assessed according to WHO guidelines. The association of unsuccessful treatment outcome with socio-demographic and clinical factors was analyzed using logistic regression model. RESULTS: Out of the 407 PTB patients (221 males and 186 females) aged 15 years and above, 89.2% had successful and 10.8% had unsuccessful treatment outcome. In the final multivariate logistic model, the odds of unsuccessful treatment outcome was higher among patients older than 40 years of age (adj. OR = 2.50, 95% CI: 1.12-5.59), family size greater than 5 persons (adj. OR = 3.26, 95% CI: 1.43-7.44), unemployed (adj. OR = 3.10, 95% CI: 1.33-7.24) and among retreatment cases (adj. OR = 2.00, 95% CI: 1.37-2.92) as compared to their respective comparison groups. CONCLUSIONS: Treatment outcome among smear-positive PTB patients was satisfactory in the Tigray region of Ethiopia. Nonetheless, those patients at high risk of an unfavorable treatment outcome should be identified early and given additional follow-up and social support.